Elements of Bantenese, Javanese And Balinese Art Carved on Lawangkori Gedongwani in East Lampung, Indonesia - Fadillah, Mohammad Ali; Ali, Mufti Ali (Badan Riset dan Inovasi Nasional (BRIN), 2024)
This research aims to reveal the Lawang Kori Gedongwani carving art in East Lampung, one of the areas in South Sumatra which since the early 17th century was the territory of the Banten Sultanate. Based on its current appearance, Lawang Kori is carved in the typical Bantenese art style that dominantly decorates pottery shards and tombstones at Banten Lama urban site. However, in certain details Lawang Kori also showed the influence of art from other regions in Java and Bali. To determine the existence of these artistic elements, research will focus on the forms and types of ornaments that were manifested in the Lawang Kori carvings, both in whole and in part. Therefore, direct observations were carried out in Gedongwani Village, Mergo Tigo District, East Lampung Regency, where Lawangkori was found. Identification of shapes and decorations produces very diverse decorative patterns. By focusing on the analysis on structure, construction and decorative elements in the form of geometric, floral and figurative motifs, Lawang Kori presented the characteristics strongly influenced by the decorative arts of Banten, East Java and Bali. Islamic art itself was the result of modifications from the Hindu-Buddhist period. Referring to historical sources and oral traditions, the Lawang Kori gate was probably made in the late 17th and early 18th centuries. The growth of port cities under the rule of the Javanese-Islamic polity stimulated the development of decorative arts in their area of influence. Islamic works of art themselves were the result of modifications from the Hindu-Buddhist period. In this case, Banten was an agent for the spread of Islamic art in the Lampung region, from its golden age to its decline in the early 19th century.